2022
DOI: 10.1186/s12889-022-14614-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing core capacities for addressing public health emergencies of international concern at designated points of entry in cameroon during the COVID-19 Pandemic

Abstract: Background Points of Entry (POEs) are at the frontline for prevention, detection and response to international spread of diseases. The objective of this assessment was to ascertain the current level of existing International Health Regulations (IHR) core capacities of designated airports, ports and ground crossings in Cameroon and identify critical gaps for capacity building for prevention, early warning and response to public health threats including COVID-19. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In India, at Jaipur International Airport, Neha, Joshi [64] reported poor cooperation among passengers, masking symptoms, apprehension and inadequate human resources as barriers to POE screening effectiveness. Similarly, other studies have reported inadequate personal protective equipment and supplies, insufficient screening infrastructure, inadequately trained staff and the existence of many informal entry points, lack of training among staff, missing information in health alert cards, lack of harmonized traveler screening measures, poor intersectoral coordination, lack of transport, absence of an public health emergency plan, and inadequate financial resources as potential challenges affecting POE health screening [65][66][67][68].…”
Section: Discussionmentioning
confidence: 92%
“…In India, at Jaipur International Airport, Neha, Joshi [64] reported poor cooperation among passengers, masking symptoms, apprehension and inadequate human resources as barriers to POE screening effectiveness. Similarly, other studies have reported inadequate personal protective equipment and supplies, insufficient screening infrastructure, inadequately trained staff and the existence of many informal entry points, lack of training among staff, missing information in health alert cards, lack of harmonized traveler screening measures, poor intersectoral coordination, lack of transport, absence of an public health emergency plan, and inadequate financial resources as potential challenges affecting POE health screening [65][66][67][68].…”
Section: Discussionmentioning
confidence: 92%
“…As seen in other African countries, few PoEs had the capacity to isolate ill travellers with suspected noti able illnesses 13,19 . This presents a risk of disease transmission between travellers at PoEs and eventual disease importation or exportation even in the presence of screening 13 .…”
Section: Coordination and Communicationmentioning
confidence: 99%
“…As of June 26, 2022, Cameroon counted 120,002 cases, leading to 1,932 deaths, and, as of March 16, 2023, the reported mortality rate for Cameroon was 7.17 per 100 000 population [7]. It has been reported that COVID-19 data in sub-Saharan African countries may be underestimated due to flaws in representativeness [8].…”
Section: Introductionmentioning
confidence: 99%
“…Early in 2020, WHO conducted a global fundraising, which led to the development of Strategic Preparedness and Response Plans (SPRP) that support and protect countries such as Cameroon with weak healthcare systems [8]. The SPRP aimed to minimize the impact of the pandemic around the world by interrupting transmission, controlling infection, and facilitating communication to limit disastrous economic and social effects [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation